2021
DOI: 10.1371/journal.pone.0252222
|View full text |Cite
|
Sign up to set email alerts
|

Shigella-specific antibodies in the first year of life among Zambian infants: A longitudinal cohort study

Abstract: Introduction Shigellosis, is a leading cause of moderate-to-severe diarrhoea and related mortality in young children in low and middle income countries (LMICs). Knowledge on naturally acquired immunity can support the development of Shigella candidate vaccines mostly needed in LMICs. We aimed to quantify Shigella-specific antibodies of maternal origin and those naturally acquired in Zambian infants. Methods Plasma samples collected from infants at age 6, 14 and 52-weeks were tested for Shigella (S. sonnei an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Two previous studies of transplacental transfer of antibodies against S. flexneri 2a and S. sonnei LPS in Israel (32) and against S. sonnei LPS in Vietnam (21) also found high levels of IgG specific for Shigella LPS in maternal sera. Our data suggest that the mothers in our cohort had been exposed to both S. flexneri 2a and S. sonnei, which is consistent with the reported serotype prevalence in countries neighboring Malawi (20,33), and other endemic regions (32,34,35). The study in Vietnam reported a much higher median transfer ratio (1.33) for S. sonnei LPS IgG (21) than was observed in our cohort, which may reflect regional differences in seroprevalence due to Shigella circulation (and possibly increased proportions of LPS-specific IgG1).…”
Section: Discussionsupporting
confidence: 91%
“…Two previous studies of transplacental transfer of antibodies against S. flexneri 2a and S. sonnei LPS in Israel (32) and against S. sonnei LPS in Vietnam (21) also found high levels of IgG specific for Shigella LPS in maternal sera. Our data suggest that the mothers in our cohort had been exposed to both S. flexneri 2a and S. sonnei, which is consistent with the reported serotype prevalence in countries neighboring Malawi (20,33), and other endemic regions (32,34,35). The study in Vietnam reported a much higher median transfer ratio (1.33) for S. sonnei LPS IgG (21) than was observed in our cohort, which may reflect regional differences in seroprevalence due to Shigella circulation (and possibly increased proportions of LPS-specific IgG1).…”
Section: Discussionsupporting
confidence: 91%
“…We cannot rule out the possibility that a host who has previously experienced mucosal exposure to Shigella antigens (e.g., children above three years of age) may be better protected by the parenteral administration of a conjugate vaccine than infants and very young children. Recent studies that we carried out on consecutive plasma samples collected from Zambian infants at the age of 6, 14 and 52 weeks are consistent with early exposure to Shigella and indicate naturally acquired IgG and IgA antibodies to S. flexneri 2a and S. sonnei LPS in a proportion of infants between 14 and 52 weeks of age [ 63 ]. At the age of nine months, targeted for the first dose of a Shigella vaccine in such settings, the oral natural priming documented by the early rise in anti-LPS antibodies may play a supportive role in the immune response and subsequent protection following the parenteral delivery of immunogenic vaccine candidates.…”
Section: Bridging From the Classical Conjugates To The Novel ...supporting
confidence: 60%
“…Furthermore, the expansion of OPS-specific immunity following challenge, regardless of disease severity, argues for a critical role for both IpaB- and OPS-specific immune mechanisms in the resolution of infection. Thus, while OPS immunity, which is highly serotype specific, dominates endemic immunity ( Chisenga et al., 2021 ; Cohen et al., 1988 ; Van De Verg et al., 1992 ), the data shown here argue that vaccines able to induce a shift in natural immunodominance of the response away from OPS-only immunity to an Ipa/OPS response may drive more robust, longer-lived cross-reactive immunity. However, it will be important to explore differences in isotype and immunodominant responses in young children living in Shigella -endemic areas who are the most vulnerable to shigellosis and harbor an evolving immune system.…”
Section: Discussionmentioning
confidence: 71%